Expression and Function of PPARs in Placenta. (12th February 2013) - Matsuda, Satoru; Kobayashi, Mayumi; Kitagishi, Yasuko
Abstract : Peroxisome proliferator-activated receptors (PPAR) are members of the superfamily of nuclear hormone receptors involved in embryonic development and differentiation of several tissues including placenta, which respond to specific ligands such as polyunsaturated fatty acids by altering gene expression. Three subtypes of this receptor have been discovered, each evolving to achieve different biological functions. The PPARs also control a variety of target genes involved in lipid homeostasis. Similar to other nuclear receptors, the transcriptional activity of PPARs is affected not only by ligand-stimulation but also by crosstalk with other molecules. For example, both PPARs and the RXRs are ligand-activated transcription factors that coordinately regulate gene expression. In addition, several mechanisms underlying negative regulation of gene expression by PPARs have been shown. It is suggested that PPARs are key messengers responsible for the translation of nutritional stimuli into changes in gene expression pathways for placental development.